Дослідження впливу акустичного екрану на запис голосу у домашніх умовах - Троїцький, М. І. (ХНУРЕ, 2023)
When recording in unsuitable conditions the problem of excessive reverberation arises. Reverberation greatly distorts the sound recording. Acoustic screens are used to reduce perceptible reverberation. The dimensions of screens of industrial manufacture are usually half the lower limit necessary for effective shielding of low frequencies. In the work, a self-made acoustic screen with dimensions of 1 m x 1 m was manufactured and studied.
Keywords: акустичний екран; голос; запис голосу; вплив акустичного екрану; запис голосу у домашніх умовах